Anaesthetists’ knowledge of central venous catheters in a department of anaesthesiology - Mukucha, Gabriel Shawn (My University, 2020)
Background Central venous catheters (CVCs) are used in the emergency department, general wards and in the peri-operative period extending into the intensive care unit (ICU). This wide usage of CVCs is accompanied by high complication rates. In South Africa there is paucity of literature regarding evaluation of healthcare workers (HCWs) knowledge of CVCs, especially amongst anaesthetists. The aim of this study was to determine the anaesthetists’ knowledge of CVCs in the Department of Anaesthesiology at the University of the Witwatersrand (Wits). Methods A prospective, contextual, descriptive research design was employed in this study using a self-administered questionnaire developed following review of the literature. The study population consisted of all anaesthetists working in the Department of Anaesthesiology at Wits. A convenient sampling method was used and completion of the questionnaire implied consent. Adequate knowledge was defined as a score above 15.5 out of 25 (62%) as determined using the Angoff method. Results The anaesthetists’ mean score was 13.1 (SD 3.1) 52.4% which showed inadequate knowledge of CVCs in the department. Of the 27 (21.4%) anaesthetists who had adequate knowledge, 17 (63%) were seniors and 10 (37%) were juniors. Seniors had a mean score out of 25 of 14.1 (SD 2.4) and juniors 12.1 (SD 3.6). Overall, seniors’ knowledge was better than juniors’ (p=0.0005) but there was no significant difference between the seniors and juniors who obtained adequate knowledge (p=0.199). Anaesthetists scored the lowest in the infection control section with a median of 4 out of 10 (40%). Conclusion The level of knowledge with regards to central venous catheters was inadequate. There is a need to improve this knowledge by providing more teaching and assessment around the subject particularly with regards to infection control measures.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology, to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2019